LAS RESERVAS PETROLERAS DE LA REPUBLICA MEXICANA - RODIGUEZ AGUILAR, M; BARNETCHE GONZALEZ, ALBERTO (My University, 1950)
no
BOL ASOC MEX GEOL PET
Keywords: RESERVAS, PETROLERAS, REPUBLICA, MEXICANA; CIENCIAS DE LA TIERRA Y DEL ESPACIO; GEOLOGIA; GEOLOGIA DEL PETROLEO